Learning Process at MTS Al-arief Jate Giliraja during the covid-19 Pandemic - Eviyatul Siska; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This study is intended to be characterized by the learning process during the al-arief pandemic in improving the learning process, methods and purposes to improve the learning process. This method of research is qualitative descriptive. The result of the study of learning strategies at Junior Hight School Al-arief were carried out offline but at the school there was a shortage of educators.